Особливості комерціалізації і трансферу технологічних інновацій виробничого призначення та боротьби з контрафактом - Войтко, Сергій Володимирович; Ілляшенко, Наталія Сергіївна (НТУ "ХПІ", 2015)
В статті розглянуто питання комерціалізації та трансферу технологічних інновацій. З позицій ринкового середовища обґрунтовано особливості здійснення цих процесів на промислових підприємствах нашої країни. Особлива увага приділена можливостям виробництва, дистрибуції та збуту контрафактної продукції. Визначено основні статті економічних збитків правовласників від порушення прав інтелектуальної власності.

In the article the questions of transfer and commercialization of technological innovation. It is proved that a pivotal position in this chain belongs to the processes of formation and feasibility of technology commercialization, identification and control of this process, the definition and justification of the methodological approaches for its improvement and development. From the standpoint of the market environment proved features of the implementation of these processes at industrial enterprises of our country. Special attention is paid to the possibilities of production, distribution and sales of counterfeit products. It is proved that an extremely important feature of contemporary processes of commercialization and transfer of intellectual technologies is the availability on the market of counterfeit goods. The article identifies the main economic losses of copyright holders from intellectual property infringement. Recommendations on the practical use of the developed regulations on industrial enterprises of our country.
Features of transfer and commercialization of technological innovations for production purposes and the fight against counterfeiting
Keywords: збитки правовласників; виключні права; промислові підприємства; інтелектуальна власність; right holders; exclusive right